Efficient solvothermal reduction of coarse-scale graphene oxide. (May 2020) - Rajabzoda, S.S.; Eremina, E.A.; Sinitsyna, O.V.; Maslakov, K.I.; Sidorov, A.V.; Kaplin, A.V.; Kolesnikov, E.A.; Savilov, S.V.; Grigorieva, A.V.
Abstract: Solvothermal reduction of graphene oxide performed up to a sp 2 /sp 3 ratio of 20 was demonstrated. The presence of chemical and structural defects was minimized by varying the treatment conditions and reduction agents to reduce their impact on electronic and optical properties. Using the interphase deposition technique both graphene oxide and reduced graphene oxide films were transferred onto ITO-coated glass substrates or SITAL for further analysis. The analysis of the electric characteristics of the reduced graphene oxide films showed high sheet resistance originated from grain boundary resistance. The optical transmittance of the films reached 30% for the most uniform coatings. Highlights: Solvothermal reduction of graphene oxide (GO) increased the sp 2 /sp 3 ratio up to 20. Pure ethanol as a solvothermal reductant for GO provided less admixtures. 10-nm-thick RGO flakes were transferred onto SITAL using oil–water interface. Sheet resistance of RGO was 2–5 × 10 6  Ω cm and varied between samples. Poor electron transfer between individual RGO flakes results in poor conductivity.